Bibliometric Analysis of STEM Robotics in Physics Education: Global Trends (2008-2024) Based on Scopus Data - Windrawan, I Gede; Wibowo, Firmanul Catur; Sugihartono, Iwan (Jurnal Ilmiah Pendidikan Fisika, 2024)
This study aims to analyze global trends in STEM-based robotic physics education through a bibliometric analysis conducted using data obtained from the Scopus database. STEM and robotics are increasingly gaining attention as effective approaches in physics education, aligning with the 21st-century demand for technical skills, creativity, and problem-solving abilities. This research utilizes R bibliometric software to identify publication patterns, researcher collaborations, and key trends in STEM-based robotic physics education from 2008 to 2024. The methods involved searching for articles using the keywords "STEM AND robotic AND physics AND education," resulting in 53 downloaded and analyzed articles. The analysis was conducted in two main steps: data collection from Scopus and metadata analysis to identify research trends and collaboration networks among researchers. The results indicated a substantial growth in the volume of publications and international collaborations, with the United States leading in publication contributions, followed by Ukraine and Colombia. The key findings reveal that recent research trends focus on learning media and STEM. Meanwhile, topics that have received less attention include the impact of STEM on the curriculum and the development of critical thinking skills. Several topics, such as augmented reality and critical thinking, were also identified as challenging potential avenues for future research. This research offers significant guidance for future researchers in developing more effective STEM-based education strategies and suggests closer collaboration between academics and practitioners in various countries. Future research is recommended to explore alternative bibliometric analysis tools and expand the database coverage to enrich perspectives and enhance the scope of findings.